A temporal examination of calcium signaling in cancer- from tumorigenesis, to immune evasion, and metastasis - MengMeng Xu; Andreas Seas; Musa Kiyani; Keven S. Y. Ji; Hannah N. Bell (Cell & Bioscience, 2018)
Abstract Background Although the study of calcium (Ca2+) is classically associated with excitable cells such as myocytes or neurons, the ubiquity of this essential element in all cellular processes has led to interest in other cell types. The importance of Ca2+ to apoptosis, cell signaling, and immune activation is of special import in cancer. Main Here we review the current understanding of Ca2+ in each of these processes vital to the initiation, spread, and drug resistance of malignancies. We describe the involvement of Ca2+, and Ca2+ related proteins in cell cycle checkpoints and Ca2+ dependent apoptosis and discuss their roles in cellular immortalization. The role of Ca2+ in inter-cellular communication is also discussed in relevance to tumor-stromal communication, angiogenesis, and tumor microinvasion. The role that Ca2+ plays in immune surveillance and evasion is also addressed. Finally, we discuss the possibility of targeting Ca2+ singling to address the most pressing topics of cancer treatment: metastatic disease and drug resistance. Conclusion This review discusses the current understanding of Ca2+ in cancer. By addressing Ca2+ facilitated angiogenesis, immune evasion, metastasis, and drug resistance, we anticipate future avenues for development of Ca2+ as a nexus of therapy.